Faunal composition and community structure of the world\'s deepest whale-fall community: shedding light on the ecological role of Osedax (Polychaeta: Siboglinidae) and whale-fall biogeography - Lucas, Joan Manel Alfaro (2015)
This study aims to describe the faunal composition and community structure of the world\'s deepest whale fall and the first found in the South Atlantic Ocean. This discovery adds very important data on the poorly known whale-fall biogeography and provides new insights on the ecological role of the \"bone-eating\" worm Osedax (Polychaeta: Siboglinidae) on associated biota. The whale fall was serendipitously found in April 24th, 2013 at the base of São Paulo Ridge at 4204 m depth in the SW Atlantic Ocean using the HOV Shinkai 6500 during the Brazil-Japan joint Iatá-Piúna Oceanographic Expedition on board RV Yokosuka (Japan Agency for Marine-Earth Science and Technology, JAMSTEC). Detailed video surveys of the carcass were made using high-definition video cameras. Vertebrae, surrounding sediments and fauna were also collected using the submersible manipulators and a slurp gun. The partial skeleton belonged to an Antarctic Minke whale, Balaenoptera bonaerensis, and was composed of nine caudal vertebrae, whose degradation state suggests it was on the bottom for at least 5 years. Most of the 41 invertebrate species found are new to science, with ca. 12% of the genera shared with NE Pacific whale falls, vent and seep ecosystems. This similarity strongly supports the hypothesis that whale falls act as \"stepping-stones\" for the dispersion of chemosynthetic fauna and that some whale-fall specialists are widespread worldwide at genus level. Detailed investigation of inner bone assemblages indicates that Osedax degradation deeply affects their diversity and structure. Bones colonized by Osedax support distinct, significantly more diverse and abundant assemblages. This renders Osedax the status of ecosystem engineer, creating new microhabitats and enhancing biodiversity in deep-sea whale-fall communities.